Teacher Growth Through Professional Development Centered on the Teaching for Robust Understanding Framework - Eileen Murray; Helene S. Leonard; Victoria D. Bonaccorso (Education Sciences)
Research on teacher learning has continually defined tenants of effective professional development. However, sweeping overhauls and mandates have not yielded the intended results. Instead, transforming approaches to teaching can and should be achieved through innovative and incremental changes that build upon teachers’ existing expertise. Informed by Communities of Practice theory, we employed case study methodology to describe, explain, and assess the experiences of one middle school mathematics teacher’s longitudinal participation in an innovative and incremental continuous PD model focused on the Teaching for Robust Understanding (TRU) framework. Based on classroom observations and interview data, our findings show evidence of TRU-aligned changes in teaching practice as a result of years of participation in the PD model. These findings strengthen the call for innovative and incremental PD programs.